2016
DOI: 10.18544/pedm-22.03.0057
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery intima-media thickness (cIMT) in young type 1 diabetic patients in relation to comorbid additional autoimmune diseases and microvascular complications

Abstract: 1. Increased value of cIMT, and thus increased risk of early disease of the cardiovascular system depends primarily on metabolic compensation and classic risk factors for atherosclerosis. 2. The coexistence of additional autoimmune disease does not significantly affect the value of cIMT in the study population. 3. Young patients with diabetes type 1 and coexisting Hashimoto disease have greater BMI and waist circumference, what can lead to earlier macroangiopathy in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…There is increasing knowledge about the prevalence of AAD in the course of long-lasting T1D in children with T1D (15,16). Notably, the association of T1D with other autoimmune illnesses that coexist from the onset of diabetes and the actual trend of this connection over the years are not fully recognized.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing knowledge about the prevalence of AAD in the course of long-lasting T1D in children with T1D (15,16). Notably, the association of T1D with other autoimmune illnesses that coexist from the onset of diabetes and the actual trend of this connection over the years are not fully recognized.…”
Section: Introductionmentioning
confidence: 99%
“…The discussion of obtained results regarding macrovascular system is limited due to the lack of other studies on properties of large arteries in corresponding pediatric cohorts. The literature review revealed only one study performed on adolescents and young adults with diabetes, which showed that the presence of additional autoimmune disease does not significantly affect the value of carotid intima-media thickness (IMT; Klonowska et al, 2016). However, the functional effects of AIT have not been studied in their research.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that obesity and T1DM in youth are associated with greater cIMT. It is also influenced by hypertension, dyslipidemia, and poor glycemic control (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%